Antiphosphatidylserine/Prothrombin Antibodies: An Update on Their Association with Clinical Manifestations of Antiphospholipid Syndrome - Radin, Massimo; Foddai, Silvia G.; Cecchi, Irene; Rubini, Elena; Schreiber, Karen; Roccatello, Dario; Bertolaccini, Maria Laura; Sciascia, Savino (Thrombosis and Haemostasis, 2020)
Objective The aim of the study is to perform a systematic review on the recent available evidence on antiphosphatidylserine/prothrombin (aPS/PT) antibodies and their association with clinical manifestations of the antiphospholipid syndrome (APS).Methods A detailed literature search was applied a priori to Ovid MEDLINE, In-Process and Other Non-Indexed Citation 2012 to present and to abstract from EULAR and ACR/ARHP Annual Meetings (2012–2019).Results Data from 2,901 patients, 587 diseases controls and 559 healthy controls included in 15 retrieved studies was analyzed. The patient population included 1,219 patients classified as APS according to the Sidney criteria, 285 patients with isolated persistently positive antiphospholipid antibodies (aPL) and 1,397 patients with a clinical suspicion of APS. Twelve studies, including 1,888 patients, analyzed the association between aPS/PT antibodies and thrombosis. We observed a statistically significant association between aPS/PT IgG/IgM positivity and thrombotic events (mean odds ratio [OR]: 6.8 [95% CI: 3.18–16.4], p < 0.05), confirmed when analyzing aPS/PT IgG (mean OR: 6.7 [95% CI: 3.04–21.6], p < 0.05) and aPS/PT IgM (mean OR: 4.35 [95% CI: 1.54–17.77], p < 0.05) separately. Seven studies, including 1,388 patients, evaluated the association between aPS/PT antibodies and PM. When pooled together, we found a statistically significant association between any PM and aPS/PT IgG/IgM positivity (mean OR: 10.6 [95% CI: 3.54–35.38], p < 0.05), particularly aPS/PT IgG positivity (mean OR: 6.7 [95% CI: 3.04–21.6], p < 0.05).Conclusion Our results highlight the strong association between aPS/PT and the clinical manifestations of APS. With the available level of evidence, aPS/PT testing can be considered as a robust test applicable in the investigation of patients suspected for APS, also beyond the research settings.
Keywords: antiphospholipid syndrome; antiphospholipid antibodies; antiphosphatidylserine; antiphosphatidylserine/prothrombin; non criteria aPL; thrombosis; autoimmunity